KESIAPSIAGAAN INDONESIA DALAM MITIGASI DAMPAK PERUBAHAN IKLIM DI INDONESIA - Natalia Yeti Puspita (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
The existence of climate change due to global warming has increased the risk of disasters in Indonesia, such as rising sea levels that cause flooding. This is certainly a threat to the people of Indonesia, especially those who live in coastal areas and small islands. Property and life losses due to climate disasters continue to increase. Indonesia's preparedness is needed to protect its citizens from climate disasters. This preparedness must take into account the guarantee of the fulfillment of human rights and justice for the environment. The more prepared and resilient a country is to the impacts of climate change, the less climate disasters there will be in that country. This article will analyze how Indonesia is prepared to deal with climate disasters. This article is the result of a normative juridical research that prioritizes secondary data as primary data. The results showed that Indonesia's preparedness was carried out by ratifying the UNFCCC, the Kyoto Protocol and the Paris Agreement through Indonesian national regulations. In addition, the Government of Indonesia cooperates and coordinates with various parties (academics, businessmen, journalists, communities) to mitigate and adapt to the impacts of climate change. It's just that until now there is no comprehensive and integrated regulation that clearly regulates climate disaster management. The current Law Number 24 of 2007 concerning Disaster Management does not explain or explicitly regulate climate disasters.